2006
DOI: 10.1007/s11274-005-9113-1
|View full text |Cite
|
Sign up to set email alerts
|

‘Morphological shifts’ in filamentous bacteria isolated from activated sludge processes

Abstract: This study aimed at isolating filamentous bacteria from full-scale activated sludge processes and studying them in pure culture. Three cultures were isolated using conventional microbiological techniques. The isolates were positively identified as Gordonia amarae, Thiothrix nivea and Type 1863/Acinetobacter spp., using fluorescent in situ hybridization (FISH) with 16S rRNA-targeted oligonucleotide probes. However, a 'morphological shift' from filamentous to single-cell form was observed in pure culture. The ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…This finding is contrary to Pike and Curds' computer simulation of microorganism succession (Pike & Curds 1971 It seems probable that grazer pressure can enhance such morphology as has been shown in aquatic bacteria (Hahn & Hö fle 2001). It has also been shown that filamentous bacteria from activated sludge are extremely plastic when isolated and grown in pure culture (Ramothokang et al 2006). The authors showed that three different filamentous bacteria changed their form to single cocci or rod-shaped cells when isolated on solid medium.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…This finding is contrary to Pike and Curds' computer simulation of microorganism succession (Pike & Curds 1971 It seems probable that grazer pressure can enhance such morphology as has been shown in aquatic bacteria (Hahn & Hö fle 2001). It has also been shown that filamentous bacteria from activated sludge are extremely plastic when isolated and grown in pure culture (Ramothokang et al 2006). The authors showed that three different filamentous bacteria changed their form to single cocci or rod-shaped cells when isolated on solid medium.…”
Section: Discussionmentioning
confidence: 82%
“…The authors showed that three different filamentous bacteria changed their form to single cocci or rod-shaped cells when isolated on solid medium. They assumed that it was a reaction to the change in environmental conditions (Ramothokang et al 2006). If bacteria can so radically change their morphology in response to habitat conditions, it is also highly probable that in their natural habitat, they can shift morphology to protect themselves against grazers.…”
Section: Discussionmentioning
confidence: 99%
“…For example some filamentous organisms are able to revert to a unicellular form at some stages of their lifecycle (Ramothokang et al, 2006). Other morphological groups such as 'Eikelboom Type 1863' have been shown to comprise of several unrelated taxa (Seviour et al, 1997) (therefore a confidence and utility score 3).…”
Section: Microscopy Based Ecologymentioning
confidence: 99%
“…Isolation of filamentous bacteria, however, is a difficult task. The majority of filamentous bacteria are overgrown by rapid growers (Ramothokang et al, 2006). Therefore, the aim of this research was to isolate, identify, and characterize the predominant filamentous bacteria observed in foaming sludge from a South African wastewater treatment plant.…”
Section: Introductionmentioning
confidence: 99%